8+3(4x-5)=6-4(2x+1)

Simple and best practice solution for 8+3(4x-5)=6-4(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+3(4x-5)=6-4(2x+1) equation:


Simplifying
8 + 3(4x + -5) = 6 + -4(2x + 1)

Reorder the terms:
8 + 3(-5 + 4x) = 6 + -4(2x + 1)
8 + (-5 * 3 + 4x * 3) = 6 + -4(2x + 1)
8 + (-15 + 12x) = 6 + -4(2x + 1)

Combine like terms: 8 + -15 = -7
-7 + 12x = 6 + -4(2x + 1)

Reorder the terms:
-7 + 12x = 6 + -4(1 + 2x)
-7 + 12x = 6 + (1 * -4 + 2x * -4)
-7 + 12x = 6 + (-4 + -8x)

Combine like terms: 6 + -4 = 2
-7 + 12x = 2 + -8x

Solving
-7 + 12x = 2 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-7 + 12x + 8x = 2 + -8x + 8x

Combine like terms: 12x + 8x = 20x
-7 + 20x = 2 + -8x + 8x

Combine like terms: -8x + 8x = 0
-7 + 20x = 2 + 0
-7 + 20x = 2

Add '7' to each side of the equation.
-7 + 7 + 20x = 2 + 7

Combine like terms: -7 + 7 = 0
0 + 20x = 2 + 7
20x = 2 + 7

Combine like terms: 2 + 7 = 9
20x = 9

Divide each side by '20'.
x = 0.45

Simplifying
x = 0.45

See similar equations:

| 1/2(7x-2) | | 19=2w-17 | | 5(x+1)-3(x+6)=40 | | 4w-8=36 | | Y/10-5=-45 | | x^2-11x+180=0 | | 1/3x-1=-1 | | N/4-4=1 | | 2(14x+27y)-4(23x-7y)=236 | | 3(x+8)=6x+2-3x+22 | | a-3/2a3:a-1/a-2 | | 1/5y-3=1 | | 6y^2-14y+8=0 | | 2x+3y-x-[8+1]= | | w/3-9=20 | | 6x+3x+12(4x+3)=x | | 15-2w=5 | | 40-5*7+11= | | 30.25(x)=59.5 | | Y/10-8=-16 | | 7x+4y=8x | | N/5-1=-2 | | 10=3m+7 | | 2=x^2-5x | | 13/7(1/4) | | 4z^2-24z+30=0 | | 12x+21=10x+26 | | 1+1-2-5+54*X= | | 2cosx+4= | | Y/3-12=-2 | | .5n+3= | | .5+3= |

Equations solver categories